The Effect of Digital Job Resources on Innovative Work Behavior Through Digital Engagement in Employees of PT ABC (Persero) East Java Distribution Unit - Dwi Wahyuni; Muhammad Fajar Wahyudi Rahman (Journal of Digital Business and Innovation Management, 2025)
This study explores the effect of digital job resources on innovative work behavior, with digital engagement serving as a mediating factor, among employees of PT ABC (Persero) East Java Distribution Unit. A quantitative approach was utilized, involving 60 participants. To analyze the data, the Partial Least Squares Structural Equation Modeling approach was applied, assisted by SmartPLS 4 and SPSS 4.0 software. The results indicate that: (1) Digital job resources do not exert a direct influence on innovative work behavior; (2) however, they significantly promote digital engagement; (3) digital engagement, in turn, has a positive impact on innovative work behavior; and (4) it serves as a significant mediator in the relationship between digital job resources and innovative work behavior.